Monomyth Pattern Manifested in The Garfield Movie by Mark Dindal (2024) - Berlina Tania Muzaky; Wahyu Budi (Indo Publishing, 2026)
This study examines the analysis of monomyth patterns manifested in the film The Garfield Movie (2024) using Joseph Campbell's Monomyth Theory. The method used in this study is descriptive qualitative to examine how the plot unfolds and the development of the main character, Garfield, in The Garfield Movie (2024). The results of this study show that the plot in this story can be represented systematically through the stages of the monomyth, starting from the ordinary world, the call to adventure, facing trials and conflicts, to the stage of returning with a transformed identity in the process of transformation, where the character experiences significant emotional changes. This transformation confirms that it is not only relevant in traditional epics but also applied in animated films through the structure of Garfield's journey from a simple character to a responsible one who embodies moral values, a sense of concern for others, and courage.